Direct Mass Measurements of Neutron-Deficient Lanthanides for Nuclear Structure Studies at the Proton Dripline - Beck, Sönke Till; Justus Liebig University Giessen (My University, 2023)
Experimental and theoretical studies of exotic nuclei, i.e., very short-lived nuclei far away from the valley of stability in the chart of nuclides, present a unique and important way to gain general understanding of the atomic nucleus and the governing interactions of its constituents. There is an intriguing interplay of strong, weak, and Coulomb interaction, yet the contributions from all fundamental forces (except gravitation) are integrated in the mass of a nucleus. This makes the mass one of its key properties, allowing to study nuclear structure and basic interactions. Studying exotic nuclei is challenging since they need to be produced first, they are short-lived (many of them have half-lives of only few seconds or even far below), they can only be produced in small quantities, and often the interesting ones are accompanied by a full zoo of other, less exotic and more abundantly produced nuclei. Therefore, powerful separation methods are needed to deal with huge amounts of non-interesting "by-products" and simultaneously obtain reliable results even for the few nuclei of interest. Moreover, the goal to extract information on basic interactions and nuclear structure requires high accuracies despite low statistics. In this work, improvements and measurements have been implemented and performed at two experiments at different accelerator facilities. In both experiments, a Multiple-Reflection Time-of-Flight Mass-Spectrometer (MR-TOF-MS), which has been build at Gießen University, is used. At the FRS Ion Catcher (FRS-IC) at GSI, Darmstadt, the improvements enabled unprecedented mass accuracies; at TRIUMF’s Ion Trap for Atomic and Nuclear sciences (TITAN) at TRIUMF, Vancouver, Canada, a novel method for mass separation was used to facilitate measurement with previously unknown nuclei. Within these measurements, a new isotope was discovered. This is the first discovery of a new isotope using a time-of-flight mass spectrometer. This demonstrates the advance of the frontier in mass measurements of exotic nuclei and the understanding of nuclear structure at the extremes. At the FRS-IC, several hardware and software elements have been upgraded. The new slow control system at the FRS-IC is running stable and ready to control, monitor and log existing and also various planned extensions of the detector setup. A procedure for systematically tuning the ion optics to unprecedented mass resolving powers R = m/∆m = 1 000 000 and beyond has been established. This enabled the measurement of several exotic nuclei with mass numbers around A = 70 close to the N = Z line. Among these measurements was the first direct mass measurements of 69-As, with only 10 events and with reduced uncertainty compared to the average of the previous indirect measurements. For one measued molecule, an accuracy of δm/m = 1.7 × 10e-8 was reached, which is the highest accuracy for MR-TOF-MS world-wide. The techniques applied at the FRS-IC have since been used at the TITAN MR-TOF-MS as well, also there leading to improved mass resolving powers. For TITAN, mass-selective re-trapping was characterized and for the first time used with exotic nuclei, enabling the direct measurement of 2 new and 2 improved ground state masses for neutron deficient Yb isotopes, the first measurement of the excitation energy of the Jπ = 11/2− isomeric state in 151-Yb and the indirect determination of 11 more ground state masses connected via α- and p-decays to two of the newly measured masses. The measurement of the mass of 150-Yb is at the same time the first discovery of a new isotope with an MR-TOF-MS. The direct ground state mass measurements of the Yb isotopes and the subsequent determination of masses of Lu isotopes have established the N = 82 neutron shell closure farthest from the valley of β-stability with unmodified shell gap; the shell structure far from the valley of stability is a key question of modern nuclear physics. The measurement of the Jπ = 11/2− isomeric state excitation energy extends a series of constant excitation energies in these odd N = 81 states, which could now be explained by deformation of the ground and isomeric states in collaboration with theorists employing state-of-the-art nuclear mean field.
Keywords: Nuclear Structure; Proton Dripline; Lanthanides; Nuclear Isomers; Mass Spectrometry; Mass Separation; Kernstruktur; Protonenabbruchkante; Lanthanoide; Kernisomere; Massenspektrometrie; Massenseparation; ddc:530